The Influence of TikTok Social Media On Language Ethics In The Modern Era - Salsabila Khazinatul Asrar; Nabilla Tasya Putri Kuswanto; Ruliano Maulana Akbar; Khawasul Ghazali; Musyaffa Akmal; Nuke Ladyna (KIRANA : Social Science Journal, 2026)
The development of social media in the digital era has a significant impact on various aspects of life, including in terms of language ethics. One popular platform is TikTok, which allows its users to share short videos and interact with many people. This study aims to examine the influence of TikTok social media on language ethics among the younger generation. The approach used is qualitative, through analysis of TikTok video content. The research findings show that TikTok encourages the use of more relaxed, informal language, and often contains slang, and increases language creativity among users. In addition, there is also a tendency to use harsh and inappropriate words, which are often considered attention-grabbing or funny. However, some users realize the importance of maintaining language ethics, especially in a professional context. This study concludes that although TikTok influences language patterns, both by introducing new languages ​​and changing the way people communicate, awareness of language ethics is still needed to maintain existing social norms. This study provides insight into the influence of TikTok as a social media on language ethics in the real world.